2020
DOI: 10.3390/environments7090069
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Interaction of Gadolinium with Several Organic Ligands and Humic Acid by Ligand Competition Using 4-(2-Pyridylazo)-Resorcinol (PAR)

Abstract: Gd3+ forms a strongly colored complex with 4-(2-pyridylazo)-resorcinol (PAR) in aqueous solutions. We characterized the Gd3+-PAR complex in order to use it as a probe of Gd3+ speciation in the presence of environmentally relevant ligands. The formation of the Gd3+-PAR complex was investigated from pH 5 to 8 in the presence of excess PAR. The absorbance of the Gd3+-PAR complex dramatically increased from pH 5 to 8 and application of the method of continuous variation indicates that the complex was primarily 1:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…(2001) and Han and Gill (2005) used competitive ligand exchange with solvent extraction to address mercury binding by dissolved organic matter from the Florida everglades. Steinberg et al. (2020) utilized competition between 4-(2-pyidylazo) resorcinol (PAR) and humic substances to assess gadolinium (Gd 3+ ) complexation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2001) and Han and Gill (2005) used competitive ligand exchange with solvent extraction to address mercury binding by dissolved organic matter from the Florida everglades. Steinberg et al. (2020) utilized competition between 4-(2-pyidylazo) resorcinol (PAR) and humic substances to assess gadolinium (Gd 3+ ) complexation.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the interaction of Gd 3+ with several organic ligands and with humic acid by ligand competition, using (PAR) ( Steinberg et al., 2020 ). PAR forms brightly colored complexes with many metals that are easily quantified by absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…toxicity (Steinberg et al, 2020;Tovar-Sanchez et al, 2018;. Port et al, 2008a).GBCAs are unintentionally destabilized during conventional or advanced water treatment yielding to rapid transmetallation of GBCAS into free toxic Gd.…”
mentioning
confidence: 99%
“…Increased Gd concentrations in water from rural areas with no MRI facilities have been attributed to many outpatients receiving MRI scans and returning home to release the Gd through their renal route(Atinkpahoun et al, 2020). The increasing Gd concentrations found in water systems and drinking water are of profound interest to both experts, policy makers, and the general public(Brünjes & Hofmann, 2020).Unfortunately, conventional and advanced wastewater treatment plants' treated water is still rich in highly stable Gd due to lack of / incomplete removal(Steinberg et al, 2020;Rogowska et al, 2018;Cyris et al, 2013). A detailed study conducted by Lena Telgmann and co-researchers in 2012 has shown that approximately ninety percent of Gd are retained post-conventional wastewater treatment (Telgmann et al, 2012; Rogowska et al,,,2018; Elizalde-González et al, 2017).…”
mentioning
confidence: 99%